Utilization of Leucaena leucocephala in Traditional Fattening Program of Bali Cattle in Amarasi - Mona Lastri Lani; Luki Abdullah; Rudi Priyanto (Faculty of Animal Science, Bogor Agricultural University, 2015)
This field study was aimed to evaluate the availability and the utility of forage on Bali cattle in Amarasi system in dry land area such as Kupang. Amarasi system is a fattening production system (paronisasi), which traditionally utilizes Leucaena leucocephala forage in dry season of Amarasi region. This field study was conducted during the period of July to December 2013 in Oesena and Merbaun Villages. The method used in this research was field survey. This type of survey was used to identify the forage availability and utility for Bali cattle; including determining the level of feed intake, measuring carrying capacity of both observe villages, and recording body weight of cattle. Cluster random sampling was applied in this study to determine sample used in the research, those were two villages with different altitudes, namely Oesena Village and Merbaun Village. Data were analyzed descriptively to describe the related existing conditions in the field. T-test was conducted to determine leucaena consumption and Bali cattle body weight in both villages. The results showed that during observation period, availability of leucaena forage for cattle was low based on dry matter intake 3.60 and 3.58 kg/head/day, which led to low consumption of cattle. Nevertheless, the use of leucaena in this system increased average body weight gain of Bali cattle up to 0.77 kg/day, due to high crude protein consumption. The conclusion of this study was the availability of leucaena as Bali cattle feed did not meet the cattle needs, but the use of leucaena increased the average of Bali cattle body weight gain.Key words: amarasi system, Bali cattle, Leucaena leucocephala, paronisasi